Reexamining the Association of Maternal Age and Marital Status at First Birth With Youth Educational Attainment. Issue 5 (19th August 2016) - Addo, Fenaba R.; Sassler, Sharon; Williams, Kristi
Abstract : We reexamined the association of maternal age and marital status at birth with youth high school completion using data from the Children and Young Adult sample of the 1979 National Longitudinal Survey of Youth and giving attention to multiple age categories and race and ethnic variations. Youth born to older teen mothers were no more likely to graduate from high school than those born to the youngest teen mothers. Although delaying childbirth to young adulthood was associated with greater odds of children's high school completion when compared with the earliest teen births, those born to young adult mothers were disadvantaged when compared with those born to mothers aged 25 years or older. Being born to an unmarried mother was associated with lower odds of high school completion. We found no evidence that maternal age at birth more strongly predicted high school graduation for White compared with Latino and Black youth.